2023
DOI: 10.23960/jtep-l.v12i1.201-211
|View full text |Cite
|
Sign up to set email alerts
|

Production of Botanical Seeds and Shallot Boobs with Vernalization and Giberrylin (GA3) Treatment in Highland Areas

Abstract: Vernalization and Gibberellin (GA3) solution can be applied to simultaneously increased shallot production and TSS (True Shallot Seed) in the highlands. The research aimed to obtain shallot varieties that are able to naturally flower more and have high growth and production. This research was carried out in the form of split plot experimental design. The main plots consisted of five shallot varieties selected from the adaptation test, which resulted from planting in the lowlands and highlands, namely the Bima … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The fresh weight and the number of bulbs of shallot varieties Lembah Palu cultivated in Central Sulawesi were around 52.52 g and 5.71 bulbs (Lasmini et al, 2022). The plant height in this study showed a more significant increase at 28 DAS than the 'Bima Brebes' cultivated in highland South Sulawesi (40 cm vs. 31.94 cm) (Idhan et al, 2023). The equivalent diameter of bulbs is also relatively bigger compared to the bulb diameter of the 'Bima Brebes' harvested from North Sulawesi province, i.e., 1.96 cm (Tandi et al, 2021).…”
Section: Resultsmentioning
confidence: 44%
“…The fresh weight and the number of bulbs of shallot varieties Lembah Palu cultivated in Central Sulawesi were around 52.52 g and 5.71 bulbs (Lasmini et al, 2022). The plant height in this study showed a more significant increase at 28 DAS than the 'Bima Brebes' cultivated in highland South Sulawesi (40 cm vs. 31.94 cm) (Idhan et al, 2023). The equivalent diameter of bulbs is also relatively bigger compared to the bulb diameter of the 'Bima Brebes' harvested from North Sulawesi province, i.e., 1.96 cm (Tandi et al, 2021).…”
Section: Resultsmentioning
confidence: 44%